Utilization of Statistical Methods in Educational Research - Rudolf, Ladislav; Barot, Tomáš (Rzeszów University Press, 2025)
Statistical methods play a key role in educational research. This paper focuses on the signifiance and application of statistical methods in educational research, demonstrating how these methods can be used to examine the effectiveness of different teaching methods, evaluate educational interventions, and identify factors influencing learning. Basic statistical procedures, such as statistics, correlations, regression analyses, t-tests, and statistical hypotheses are discussed. The paper also highlights common errors in the use of statistical methods and stresses the importance of carefully selecting appropriate statistical tools. The aim is to provide educators and researchers with a practical overview.
Keywords: statistical method; educational research; weighted regression; hypothesis; result